A rare case of vulvar cancer in a young woman - V. G. Cherenkov; I. V. Aleksandrova; A. B. Petrov; Ye. S. Yegorova (Опухоли женской репродуктивной системы, 2014)
The paper describes a rare case of invasive vulvar cancer in a young woman. Her medical history shows that cancer ulcer appeared 3 years ago; due to the fact that vulvar cancer is extremely rare, no sample from the 25-year-old woman during her visit to an obstetrician/gynecologist was taken to be microscopically examined. When the patient came to another regional oncology dispensary, she underwent only radiotherapy (the cumulative focal dose was 60 Gy). Symptomatic therapy for prolonged tumor growth was proposed. The woman was operated on with cutaneous- fascial plasty in the Novgorod Regional Clinical Oncology Dispensary. Primary intention healing occurred with a relatively good cosmetic result.